2005
DOI: 10.1002/nbm.966
|View full text |Cite
|
Sign up to set email alerts
|

Dimethyl sulfone in human cerebrospinal fluid and blood plasma confirmed by one‐dimensional 1H and two‐dimensional 1H‐13C NMR

Abstract: (1)H-NMR spectroscopy at 500 MHz was used to confirm that a previously unidentified singlet resonance at 3.14 ppm in the spectra of cerebrospinal fluid and plasma samples corresponds to dimethyl sulfone (DMSO(2)). A triple resonance inverse cryogenic NMR probe, with pre-amplifier and the RF-coils cooled to low temperature, was used to obtain an (1)H-(13)C HSQC spectrum of CSF containing 8 microM (753 ng/ml) DMSO(2). The (1)H-(13)C correlation signal for DMSO(2) was assigned by comparison with the spectrum from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
79
0
3

Year Published

2007
2007
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 85 publications
(88 citation statements)
references
References 22 publications
(22 reference statements)
6
79
0
3
Order By: Relevance
“…Two separate studies performed by Cottler-Fox and coworkers [239] and Wever and co-workers [240] found that Me 2 SO 2 was present in human plasma and cerebrospinal fluid ranging from 0 to 25 lM. Me 2 SO 2 was also detected by magnetic resonance spectroscopy in the brains of patients with memory loss and in normal patients given doses of 1-3 g/day [241].…”
Section: Antioxidant and Pro-oxidant Effects Of Oxo-sulfur Compounds mentioning
confidence: 94%
“…Two separate studies performed by Cottler-Fox and coworkers [239] and Wever and co-workers [240] found that Me 2 SO 2 was present in human plasma and cerebrospinal fluid ranging from 0 to 25 lM. Me 2 SO 2 was also detected by magnetic resonance spectroscopy in the brains of patients with memory loss and in normal patients given doses of 1-3 g/day [241].…”
Section: Antioxidant and Pro-oxidant Effects Of Oxo-sulfur Compounds mentioning
confidence: 94%
“…Plasma samples were prepared for 1 H NMR spectroscopy with minimal handling as described [12]. For statistical analyses of the whole metabolic profile, spectra were data reduced in numerical format by integrating spectral regions (buckets) every 0.02 ppm (parts per million) and scaled to the total intensity of the spectrum with Amix 3.6.8 software (Bruker Analytische Messtechnik, Germany) from 0.8 to 8.6 ppm; the water peak area was excluded from each spectrum (4.4 to 5.2 ppm).…”
Section: Methodsmentioning
confidence: 99%
“…The four remaining metabolites, citric acid, creatine, dimethylsulfone and fructose, all display elevated levels in PD patients when compared to controls. Dimethylsulfone is involved in the methanethiol pathway, in which it is produced as a breakdown product of the nitric oxide synthase cofactor methanethiol (Engelke et al 2005). Fructose is linked to the mannose and fructose pathway, and citric acid to numerous metabolic pathways; future studies of larger patient cohorts will clarify their importance.…”
Section: Pd Patients Compared To Control Subjectsmentioning
confidence: 99%